2021
DOI: 10.1101/2021.01.03.425156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High quality mapping of chromatin at or near the nuclear lamina for small numbers of cells

Abstract: A large fraction of heterochromatin in the metazoan genome is associated with the nuclear lamina (NL) in interphase nuclei. This heterochromatin is often referred to as Lamina-Associated Domains (LADs) and are often mapped from cell populations asynchronously progressing through the cell cycle. We and others have recently reported that LADs are largely stable during G1, S, or G2 phases of the cell cycle, and appear similar to LADs mapped from bulk cell populations. LADs in senescent cells, however, are reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…We analyzed the Hi-C dataset obtained from the asynchronously dividing HCT116 cells (24) using10 sub-compartments (Figure 5A). Recently we have developed a chromatin pull-down based Tyramide-Signal Amplification sequencing (cTSA-seq) method to analyze LADs at different cell cycle stages using the human HCT116 cell line (25). We found that during early G1 the chromatin associated with the reforming NL are the sub-telomeric regions.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the Hi-C dataset obtained from the asynchronously dividing HCT116 cells (24) using10 sub-compartments (Figure 5A). Recently we have developed a chromatin pull-down based Tyramide-Signal Amplification sequencing (cTSA-seq) method to analyze LADs at different cell cycle stages using the human HCT116 cell line (25). We found that during early G1 the chromatin associated with the reforming NL are the sub-telomeric regions.…”
Section: Resultsmentioning
confidence: 99%